Lipopolysaccharide Adsorbed to the Bio-Corona of TiO2 Nanoparticles Powerfully Activates Selected Pro-inflammatory Transduction Pathways - Bianchi, Massimiliano G.; Allegri, Manfredi; Chiu, Martina; Costa, Anna L.; Blosi, Magda; Ortelli, Simona; Bussolati, Ovidio; Bergamaschi, Enrico (Frontiers in Immunology, 2017)
It is known that the adsorption of bioactive molecules provides engineered nanoparticles (NP) with novel biological activities. However, the biological effects of the adsorbed molecules may also be modified by the interaction with NP. Bacterial lipopolysaccharide (LPS), a powerful pro-inflammatory compound, is a common environmental contaminant and is present in several body compartments such as the gut. We recently observed that the co-incubation of LPS with TiO2 nanoparticles (NP) markedly potentiates its pro-inflammatory effects on murine macrophages, suggesting that, when included in a NP bio-corona, LPS activity is enhanced. To distinguish the effects of adsorbed LPS from those of the free endotoxin, a pellet fraction, denominated P25/LPS, was isolated by centrifugation from a mixture of P25 TiO2 NP (128 microg/ml) and LPS (10 ng/ml) in the presence of fetal bovine serum. Western Blot analysis of the pellet eluate indicated that P25/LPS fraction contained, besides proteins, also LPS, pointing to the presence of LPS-doped NP. The effects of adsorbed or free LPS were then compared in Raw264.7 murine macrophages. RT-PCR was used to evaluate the induction of cytokine genes, whereas active, phosphorylated isoforms of proteins involved in signaling pathways were assessed with Western Blot. At a nominal LPS concentration of 40 pg/ml of LPS, P25/LPS induced the expression of both NF-kappaB and IRF3 dependent cytokines at levels comparable to those observed with free LPS (10 ng/ml), although with different time courses. Moreover, compared to free LPS, P25/LPS caused a more sustained phosphorylation of p38 MAPK and a more prolonged induction of STAT1-dependent genes. Cytochalasin B partially inhibited the induction of Tnfa by P25/LPS, but not by free LPS, and suppressed the induction of IRF3-dependent genes by either P25/LPS or free LPS. These data suggest that, when included in the bio-corona of TiO2 NP, LPS exhibits enhanced and time-shifted pro-inflammatory effects. Thus, in assessing the hazard of NP in real life, the enhanced effects of adsorbed bio-active molecules should be taken into account.